2017
DOI: 10.3390/su9010131
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of Reinforced RCA Concrete Beams Made by a Modified EMV Method

Abstract: Abstract:This study aims to show the effect of a modified equivalent mortar volume (EMV) method on the flexural performance of recycled concrete aggregate (RCA). To verify this, an experimental study was carried out firstly by testing fresh and hardened material properties of RCA concrete specimens made by two different mixture design methods, i.e., the modified EMV method and the conventional American Concrete Institute (ACI) method. The flexural performance of five reinforced recycled concrete (RRC) beams mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Research efforts have been dedicated to characterizing the properties of RRC beams and columns in static loading conditions. The influence of RCAs on the monotonic shear [11][12][13][14][15][16][17][18][19][20][21][22][23] or flexural [24][25][26][27][28][29][30][31][32][33][34][35] behaviors of RRC beams has also been extensively experimentally investigated, with the replacement ratio (i.e., r) varied from 0% to 100%. The experimental outcomes indicate that: (i) in either shear or flexural failure, the presence of various RCA replacement ratios only has a limited influence on the damage process and failure pattern of RRC beams; (ii) an increased replacement ratio appears to reduce the load-carrying capacity of RRC beams.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts have been dedicated to characterizing the properties of RRC beams and columns in static loading conditions. The influence of RCAs on the monotonic shear [11][12][13][14][15][16][17][18][19][20][21][22][23] or flexural [24][25][26][27][28][29][30][31][32][33][34][35] behaviors of RRC beams has also been extensively experimentally investigated, with the replacement ratio (i.e., r) varied from 0% to 100%. The experimental outcomes indicate that: (i) in either shear or flexural failure, the presence of various RCA replacement ratios only has a limited influence on the damage process and failure pattern of RRC beams; (ii) an increased replacement ratio appears to reduce the load-carrying capacity of RRC beams.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the elastic modulus increases as the volume fraction of the aggregate increases [59]. In many studies, it has been reported that the compressive strength of RAC designed with the EMV mix design was lower than that of control concrete, but the elastic modulus was higher [18,27,28,60].…”
Section: Elastic Modulusmentioning
confidence: 99%
“…For the sake of sustainability, various recyclable materials (concrete, brick, glass) and industrial by-products (steel and furnace slag) have been studied as substitutes for natural aggregates (NA) [15,16]. In particular, real-scale experiments have been performed to evaluate the applicability of concrete containing recycled concrete aggregate (RCA) and materials such as electric arc furnace slag for reinforced concrete elements [17,18]. Although the applicability of recyclable materials as a substitute for NA is obvious, a difference has been observed in the replacement ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the relationship between the residual mortar content (RMC) on RA and the density and water absorption of RA investigated in other studies. There may be differences depending on production processes and the impurities contained in aggregates, in general, as the RMC increases, the specific gravity decreases and the water absorption rate tends to increase [3,13,33,35,36,[38][39][40][41][42][43][44].…”
Section: Recycled Aggregatementioning
confidence: 99%